FAKTOR – FAKTOR YANG MEMPENGARUHI KUNJUNGAN WISATAWAN KE KAWASAN EKOWISATA DI DESABAHOI KECAMATAN LIKUPANG BARAT KABUPATEN MINAHASA UTARA - Jecqerel Rio Lakuhati; Paulus A. Pangemanan; Caroline B. D. Pakasi (AGRI-SOSIOEKONOMI, 2018)
This study aims to determine the factors - factors that affect tourist visits to the ecotourism area in the village of Bahoi. This research was conducted in May - July 2016, in Bahoi Village, West Likupang Sub-district, North Minahasa Regency. The location of this study was chosen with several considerations, namely: Bahoi Village is one of the areas that have ecotourism area that is enough to attract the interest of the surrounding community and even the foreign community. Where this ecotourism area is one of the livelihood for the people of Bahoi Village. The method used in this study is the accidental sampling method by accidental interviewing technique, ie anyone who by chance there is a research location used as a sample or research respondents. The results obtained that factors affecting tourist visits are distance traveled, age level, travel expenses, and entrance fees. Where the tendency of tourists to ecotourism diving is strongly influenced by the age level because the statistical test states that the age level is very significant. While the tendency to visit ecotourism mangrove factor that most influence is the age level, because statistical test states that age is very significant.